Morphological Attributes and Yield of Momordica charantia (Bitter Gourd) Under the Application of Spiritual Blessing/Biofield Energy Treatment (BET) - Kumar Trivedi, Mahendra; Trivedi, Dahryn; Branton, Alice; Dattaram Kadam, Vivek; Rajendra Phutankar, Nikhil; Bapu Gaikwad, Tejas; Mondal, Sambhu; Jana, Snehasis (Journal of Farming, 2026)
Objective Bitter gourd (Momordica charantia L.) is a widely consumed vegetable. This study aimed to assess the impact of spiritual blessing (biofield) energy treatment (S/BET) known as the Trivedi Effect® on a plant’s growth and yield when applied to both seeds and soil. Methods Seeds were split into two groups: an untreated control group (CONBIGG) and a BET-group (BTBIGG). Soil texture was checked by hand, and mineral contents were measured using standard procedures. An experienced scholar noted plant morphological, phenological, and yield-related parameters. Results The S/BET group showed improvements in stem length, fruit colour, and seediness compared to the control. Other phenological parameters, such as vine length (38.78 %; p ≤ 0.001), branch number (54.03 %; p ≤ 0.01), inter-nodal length (42.94 %; p ≤ 0.001), fruit length (33.27 %; p ≤ 0.001), seed length (40.32 %; p ≤ 0.001), seeds per fruit (52.50 %; p ≤ 0.001), and fruits per vine (66.88 %; p ≤ 0.001), were significantly increased in the BTBIGG group compared to the CONBIGG. Yield per hectare rose by 61.31 % in the S/BET group compared to the control. Conclusion The study results suggest that the spiritual blessing/prayers/BET-Trivedi Effect® significantly improved morphological, phenological, and yield-related parameters compared to the control group. This study provides useful scientific research data and information for producing stable, high-quality bitter gourds.
Keywords: bitter gourd farming; spiritual blessing; plant morphology; crop phenology; yield; prayers